Case-control investigation of occupational lead exposure and kidney cancer. Issue 7 (13th February 2019) - Callahan, Catherine L; Friesen, Melissa C; Locke, Sarah J; Dopart, Pamela J; Stewart, Patricia A; Schwartz, Kendra; Ruterbusch, Julie J; Graubard, Barry I; Chow, Wong-Ho; Rothman, Nathaniel; Hofmann, Jonathan N; Purdue, Mark P
Abstract : Objectives: Lead is a suspected carcinogen that has been inconsistently associated with kidney cancer. To clarify this relationship, we conducted an analysis of occupational lead exposure within a population-based study of kidney cancer using detailed exposure assessment methods. Methods: Study participants (1217 cases and 1235 controls), enrolled between 2002 and 2007, provided information on their occupational histories and, for selected lead-related occupations, answered questions regarding workplace tasks, and use of protective equipment. Industrial hygienists used this information to develop several estimates of occupational lead exposure, including probability, duration and cumulative exposure. Unconditional logistic regression was used to compute ORs and 95% CIs for different exposure metrics, with unexposed subjects serving as the reference group. Analyses were also conducted stratifying on several factors, including for subjects of European ancestry only, single nucleotide polymorphisms in ALAD (rs1805313, rs1800435, rs8177796, rs2761016), a gene involved in lead toxicokinetics. Results: In our study, cumulative occupational lead exposure was not associated with kidney cancer (OR 0.9, 95% CI 0.7 to 1.3 for highest quartile vs unexposed; ptrend =0.80). Other lead exposure metrics were similarly null. We observed no evidence of effect modification for the evaluated ALAD variants (subjects of European ancestry only, 662 cases and 561 controls) and most stratifying factors, although lead exposure was associated with increased risk among never smokers. Conclusions: The findings of this study do not offer clear support for an association between occupational lead exposure and kidney cancer.